Psychological , Behavioral and Performance impact of corporal Punishment in Somaliland Students - Sakarie Mustafe Hidig; Abdiwahab Mohamed Saed (Journal of Medical Education and Family Medicine)
Objective: This study examines the use of CP in Somaliland schools and the psychological and behavioral impact of this practice on students as well as the impact of the practice on the performance of the student.Methods: This study used a qualitative study design in which a structured questionnaire was used to collect the necessary data regarding the study subject matter, and the data were analyzed via SPSS version 20 (IBM SPSS Corp., Armonk, NY, USA)Results: This study revealed a shocking prevalence of corporal punishment among Somaliland students. The study also demonstrated a strong link and statistical significance between corporal punishment and the psychological state of the students, as well as a positive relationship between corporal punishment and the behavior of the student. However, regarding the performance of the student, the study failed to find a reasonable statistical significance between this parameter and corporal punishment.Conclusion: There is a strong correlation between corporal punishment and the adverse psychological effects discussed in this study. The study also revealed a strong relationship between corporal punishment and the possible behavior issues of the pupils. The study highlighted a drawback of corporal punishment and a shift to alternatives among schools in Somaliland. Such alternatives may include positive reinforcement, rewarding good behavior, guidance and counseling, involving parents, time-outs, detentions, suspensions, motivations, recognition and praise tactics, revoking or taking away privileges, use of assignments and additional tasks such as punishment, and many other known methods as alternatives to corporal punishment.